2021
DOI: 10.1177/15459683211005028
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Walking Speed and the Energetic Cost of Walking in Persons With Multiple Sclerosis and Healthy Controls: A Systematic Review

Abstract: Background Persons with multiple sclerosis (pwMS) experience walking impairments, characterized by decreased walking speeds. In healthy subjects, the self-selected walking speed is the energetically most optimal. In pwMS, the energetically most optimal walking speed remains underexposed. Therefore, this review aimed to determine the relationship between walking speed and energetic cost of walking (Cw) in pwMS, compared with healthy subjects, thereby assessing the walking speed with the lowest energetic cost. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
(140 reference statements)
1
11
0
Order By: Relevance
“…Accepting previous evidence on the energetically optimal speed, it can be suggested that the subjects in our study also walked below their energetically optimal speed. (Theunissen et al, 2021) While walking speed increased during the 6MWT, the Cw was expected to decrease. It should however be noted that the individual Cw curves are not the scope of this study and that our subjects were asked to walk at a maximal speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accepting previous evidence on the energetically optimal speed, it can be suggested that the subjects in our study also walked below their energetically optimal speed. (Theunissen et al, 2021) While walking speed increased during the 6MWT, the Cw was expected to decrease. It should however be noted that the individual Cw curves are not the scope of this study and that our subjects were asked to walk at a maximal speed.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with MS walk at a greater Cw compared to healthy persons (Stella et al, 2020) but with a similar optimal speed, as described by the U-shaped relationship between walking speed and the Cw. (Theunissen et al, 2021) Since walking is energetically more demanding in pwMS, an increased Cw might be accompanied by changes in gait parameters. Evaluating this simultaneously will contribute to the understanding of both physical and perceived fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the benefits of exercise restore locomotory performance to levels comparable to control individuals is uncertain. Regardless of the exact mechanism, the slower gait speeds in pwMS could be explained in-part by the increase in metabolic effort as speed is reduced to minimize costs (36, 74).…”
Section: Discussionmentioning
confidence: 99%
“…Both preferred walking and reaching speeds are often selected to minimize the cost of transport (J kg −1 m −1 ) of the movement (33, 47, 71). Recent evidence suggests that pwMS minimize walking cost of transport when selecting preferred speeds (45, 74), but that the costs tend to be more expensive than controls. Measuring preferred walking and reaching speeds in this study would have also revealed whether our cohort of pwMS were selecting slower speeds than our HCs.…”
Section: Discussionmentioning
confidence: 99%
“…53 Another worthwhile measure would be the energetic cost of walking, which is based on oxygen consumption during walking. 54 Several studies have recently described associations of sensor-based outcomes during gait trials with perceived state fatigability (ratings of fatigue while performing a task), 55 objective motor fatigability (deterioration of objective performance during a motor task), 52 and trait fatigue (self-report of fatigue experienced over a longer time-period (eg, several weeks)). 12,52 Sensor-based and fatigue-related outcomes of intervention studies applying MAT should be compared to more traditional, unimodal types of exercise (ie, aerobic, or resistance exercise) to confirm that incorporating more sensory and cognitive stimuli is superior in affecting these outcomes, and potentially superior as a reserve-building activity.…”
Section: Recommendationsmentioning
confidence: 99%